TUTORIAL MODEL PROGRAM AKREDITASI TUTOR I (PAT-UT) I DAN STUDENT TEAM ACHIEVEMENT DIVISION (STAD) DITINJAU DARI MOTIVASI BELAJAR MAHASISWA - Fadloli Fadloli (LPPM Universitas Terbuka, 2011)
This article was written based on research that aims to determine: 1) Effect of the use of a tutorial model I Tutor Accreditation Program (PAT-UT I) and Student Team Achievement Division (STAD) on the course of elementary school science teaching and learning; 2) Effect of learning motivation; and 3) the interaction of two tutorial models (UTs Tutor Accreditation Program 1/PAT-UT I and Student Team Achievement Division /STAD) with the learning motivation and learning achievement. This study used experimental method of two-way factorial design (ANAVA 2 x 3). This study involved two groups, which were PAT-UT I group and STAD group. Data was collected by means of questionnaires and multiple choice learning achievement tests. The results showed (with significance level (?) 5%): 1) tutorial model has a significant effect on learning achievement attained by students; 2) learning motivation influenced learning achievement significantly; 3) there were no interaction between the tutorial model, learning motivation, and learning achievement. It was concluded that learning achievements of students with STAD tutorial model were better compared to PAT-UT I tutorial model. Higher learning motivations were resulted in higher learning achievements and learning outcomes.